Exploring Gen Z’s Interest In Islamic Banking Products: The Role Of Islamic Financial Literacy As A Mediator - Ningrum Lutfia Fatma; Diana Nur; Alrasyid Harun; Afifudin (SHS Web of Conferences, 2025)
This study investigates the factors influencing Generation Z’s intention in Indonesia to adopt Islamic banking products, focusing on awareness, social influence, perceived ease of use, and Islamic financial literacy. Despite the rapid growth of Islamic banking globally and in Indonesia, a significant gap persists between conventional and Islamic banking adoption rates. The study gathered data from 230 participants aged between 17 and 27 years, which was subsequently analyzed utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that social influence and perceived ease of use significantly and positively impact the intention to utilize Islamic banking products. Conversely, awareness does not have a notable effect on this intention, and Islamic financial literacy does not serve as a mediator in the relationships between awareness, social influence, or perceived ease of use and the intention to adopt Islamic banking. These findings emphasize the critical importance of social influence and ease of use while highlighting the necessity for improved awareness campaigns and financial literacy initiatives. Strengthened strategies in these areas could address existing gaps and foster increased adoption of Islamic banking products among Generation Z.